Texte : mit einem Gruss von Günther Uecker. - Honisch, Dieter; Uecker, Günther (Ostfildern-Ruit : Cantz Verlag Ostfildern-Ruit, 1992)
Arakawa, Shusaku ; Baumeister, Willi ; Beuys, Joseph ; Bill, Max ; Ceroli, Mario ; Dix, Otto ; Fruhtrunk, Günter ; Geiger, Rupprecht ; Giacometti, Alberto ; Graubner, Gotthard ; Hodler, Ferdinand ; Hrdlicka, Alfred ; Imdahl, Max ; Justi, Ludwig ; Kiefer, Anselm ; Kirchner, Ernst Ludwig ; Klein, Yves ; Lechner, Alf ; Lenk, Thomas ; Louis, Morris ; Luther, Adolf ; Mack, Heinz ; Morgner, Wilhelm ; Newman, Barnett ; Opalka, Roman ; Pfahler, Georg Karl ; Picasso, Pablo ; Rainer, Arnulf ; Richter, Gerhard ; Schumacher, Emil ; Serra, Richard ; Stella, Frank ; Thieler, Fred ; Trökes, Heinz ; Tschudi, Hugo von ; Uecker, Günther ; Uhlmann, Hans ; Vostell, Wolf
Duits
boek